SELECTION OBJECTIVES FOR HUACAYA ALPACA BREEDING UNDER TWO ECONOMIC SCENARIOS IN THE CENTRAL HIGHLANDS OF PERU - Candio Lopez , Julissa Raquel (2021)
The research consisted in determining the selection objectives for raising alpacas under two economic scenarios at the San Pedro de Racco Community Cooperative. The study was carried out in three stages: The first one described the alpaca’s breeding system, in the second one the elaboration of the profit equation was done, and in the third one the relative economic values by partial derivation were calculated and the selection objectives were determined. Economic scenarios 1 and 2 were defined by the payment method of the fiber. The relative economic values of fleece weight (FW) and fleece weight at the first shearing (FW1) were S/10.6 and S/5.85, respectively, values which were equal for both economic scenarios. The fiber diameter (FD) obtained values of -S/2.12 in economic scenario 2. The selection objective by economic scenarios was defined by FW, FW1, and live weight at first shearing (LW1S) for scenario 1; and by FW, FW1, and FD for scenario 2. It was concluded that the payment by categorized fiber favored the relative economic value of the fiber diameter and fiber diameter at the first shearing, contributing to the thinning of the fleeces; while the fleece weight was the character of greatest relative economic value in the selection objectives of economic scenarios 1 and 2.